THE ANALYSIS OF THE ACCUMULATION OF FOUR KINDS OF ATMOSPHERIC POLLUTION ELEMENTS IN FIFTEEN KINDS OF LANDSCAPE PLANT LEAVES - B. Liu; Y. Zhou; Y. Li (Journal of Animal and Plant Sciences, 2015)
This paper aims to reveal the difference of foliage sulfur content in common road green trees in Nanjing. Fifteen afforestation trees were selected from four sampling sites, and the sulfur content of the leaves was analyzed. The results indicate that there is a significant difference in the amount of foliage sulfur content for different species of trees at different sites. The foliage sulfur content near Chemical Works and Door of Taiping-Beijing East Road is higher than those near NanjingForestryUniversity and ZhongshanBotanical Garden. The seasonal variation of sulfur content for some trees is also evident. The sulfur content of the majority of trees, with the exception of LigustumLucidum and Viburnum awabuki, increases according to the season. Tree species have been sorted using three classifications on the basis of year-round foliage sulfur content. Populus Canadensis, Ligustrunquihoui, and Platanushispanica are classified into the first category, where the sulfur content was high. The second category includes Osmanthusfragrans, Lorpetalumchinense, andLigustumLucidum, and those varieties displayed a moderate sulfur content. Viburnum awabukiare,Cinnamomumcamphora,Buxussinica and Aucubajaponica.Var. variegate are classified into the third category, which means that their sulfur content was low.
Keywords: Landscape plant; Foliage; Pollution elements; Accumulation